Edukasi dan konseling Antenatal Care Terhadap Tingkat Pendidikan Dan Sikap Ibu Hamil Di Wilayah Kerja Puskesmas Tobadak - Manuntungi, Andi Ernawati; Parwati, Dewi; Susiandari, Ariawati; Sallo, Andi Kamal M. (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Health services during pregnancy are important for pregnant women and the fetus they are carrying. This service effort is a prevention of bad conditions that can occur in pregnant women. One of the factors that influences health outcomes for both mother and fetus is Antenatal Care. According to the District Health Service, in the Strategic Plan the Health Service identified problems based on the duties and functions of the District Health Service services related to maternal and child health, namely that health services for K4 pregnant women are still not optimal and pregnant women still find Chronic Energy Deficiency, one of which is that not all pregnant women receive maternal and child health services according to standards. Related to these reasons, a community service program was carried out in the form of Integrated Antenatal Care education and counseling for pregnant women. The results of implementing community service activities include enthusiastic pregnant women and increased knowledge with Integrated Antenatal Care examinations and providing counseling education regarding pregnancies, especially those at risk. With the existence of Integrated Antenatal Care counseling activities to improve the health level of the mother and fetus during pregnancy to prevent complications during pregnancy, more and more pregnant women are aware of the importance of Integrated Antenatal Care examinations which will increase the mother's concern for her pregnancy.